ALMA twenty-six arcmin2 survey of GOODS-S at one millimeter (ASAGAO). Issue Volume 15:Issue S352(2019) (June 2019) - Hatsukade, B.; Kohno, K.; Yamaguchi, Y.; Umehata, H.; Ao, Y.; Aretxaga, I.; Caputi, K. I.; Dunlop, J. S.; Egami, E.; Espada, D.; Fujimoto, S.; Hayatsu, N.; et al.
Abstract: The ALMA twenty-six arcmin 2 survey of GOODS-S at one millimeter (ASAGAO) is a deep (1 σ ∼ 61 μ Jy/beam) and wide area (26 arcmin 2 ) survey on a contiguous field at 1.2 mm. By combining with archival data, we obtained a deeper map in the same region (1 σ ∼ 30 μ Jy/beam −1, synthesized beam size 0.59″ × 0.53″), providing the largest sample of sources (25 sources at 5 σ, 45 sources at 4.5 σ ) among ALMA blank-field surveys. The median redshift of the 4.5 σ sources is 2.4. The number counts shows that 52% of the extragalactic background light at 1.2 mm is resolved into discrete sources. We create IR luminosity functions (LFs) at z = 1–3, and constrain the faintest luminosity of the LF at 2 < z < 3. The LFs are consistent with previous results based on other ALMA and SCUBA-2 observations, which suggests a positive luminosity evolution and negative density evolution.